Melatonin administered postoperatively lowers oxidative stress and inflammation and significantly recovers heart function in patients undergoing CABG surgery - Neshat Mohammadi; Mehdi Alizadeh; Samad Akbarzadeh; Mikaeeil Rezaei; Marzieh Mahmoodi; Thomas Netticadan; Ali Movahed (European Journal of Medical Research)
Abstract Background This study aimed to assess the effect of oral melatonin consumption on improving heart function and reducing postoperative complications in patients undergoing coronary artery bypass grafting (CABG) surgery. Methods A total of 60 CABG patients in the postoperative period were included in this randomized, double-blind, placebo-controlled trial. The patients were divided into three groups: Group 1 (n = 20, 5 mg melatonin), Group 2 (n = 20, 10 mg melatonin), and the placebo group (n = 20). The patients were discharged about 8 to 10 days after the surgery. Blood samples were taken from all the patients before and after the intervention (for 60 days), and Biochemical parameters including creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH), malondialdehyde (MDA), tumor necrosis factor alpha (TNF-α), total antioxidant capacity (TAC), nitric oxide (NO) assessed. Echocardiography and the measurement of systolic and diastolic blood pressure were also performed on participants. Results Our results showed that melatonin treatment significantly increased the ejection fraction (%EF) and TAC levels in both the treatment groups compared to the placebo group (P < 0.05). Moreover, the levels of inflammatory and oxidative biomarkers, including TNF-α, MDA, and NO, decreased in the intervention group significantly (P < 0.05). In the placebo group, %EF decreased significantly (P = 0.042), while MDA increased (P < 0.001) and TAC decreased (P = 0.002). No significant changes were observed in LDH and CK-MB levels. The comparison of serum biomarkers between the two treatment groups showed that 10 mg of melatonin was more effective than 5 mg, but the difference was not significant (P > 0.05). Conclusion The present study showed that as a potential antioxidant, melatonin could alleviate oxidative stress and inflammation associated with CABG and is essential in improving overall heart function. Trial registration: IRCT20111119008129N14, first trial registration date: 01/08/2023.